Comparison of the class estimators to some estimators by the mean square error matrix criteria - (:unkn) unknown (My University, 2018)
The ordinary least squares, the principal components regression and the Liu-type estimators are special cases ofthe r-(k,d) class estimators, for regression models with multicollinearity. In this article we derived conditions forthe superiority of the r-(k,d) class estimator over other estimators such as ordinary least squares, principalcomponent and Liu-type estimator based on the mean square error matrix (MSEM) criterion. Finally, anumerical example and a Monte Carlo simulation are also given to show the theoretical results.

En küçük kareler, temel bileşenler ve Liu-tipi tahmin ediciler, çok değişkenli regresyon modelleri için r-(k,d) sınıf tahmin edicilerin özel durumlarıdır. Bu makalede r-(k,d) sınıf tahmin edicisini, en küçük kareler, temel bileşenler ve Liu-tipi tahmin ediciler ile Matris Hata kareler ortalaması kriterine göre karşılaştırılmıştır. Son olarak teorik sonuçları göstermek için sayısal bir örnek ve bir Monte Carlo simülasyonu verilmektedir.
r-(k,d) sınıf tahmin edicisinin, ortalama karesel hata kriterine göre bazı yanlı tahmin ediciler ile karşılaştırılması
Keywords: İstatistik ve Olasılık